1999
DOI: 10.1111/j.1530-0277.1999.tb04353.x
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Acute Responses to Clamped Alcohol Concentration and Family History of Alcoholism

Abstract: The BrAC clamping paradigm assesses initial and adaptive responses of a battery of behavioral and electrophysiological measures of frontal lobe function to ethanol that appear both reliable and sensitive to FHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Other research has shown indications for acute tolerance to stable alcohol levels in a small subject sample [32], but the obtained average alcohol level was less constant than the pseudo-steady state concentrations presented here. A few groups were able to generate accurate and stable alcohol levels by clamping the BrAC according to the original O'Connor procedure [2], and reported acute tolerance to constant alcohol levels, particularly for subjective measurements [33][34][35]. However, these findings were based on only two measurements throughout the steady-state periods.…”
Section: Figure 10mentioning
confidence: 58%
“…Other research has shown indications for acute tolerance to stable alcohol levels in a small subject sample [32], but the obtained average alcohol level was less constant than the pseudo-steady state concentrations presented here. A few groups were able to generate accurate and stable alcohol levels by clamping the BrAC according to the original O'Connor procedure [2], and reported acute tolerance to constant alcohol levels, particularly for subjective measurements [33][34][35]. However, these findings were based on only two measurements throughout the steady-state periods.…”
Section: Figure 10mentioning
confidence: 58%
“…Furthermore, venous blood measurements of the drug concentration often do not reflect the drug concentration in the brain (Wu et al 2001;. To circumvent these methodological problems, a compelling rationale has been made for measuring acute tolerance at steady-state drug concentrations for ethanol (Ramchandani et al 1999;Froehlich et al 2001) and for other drugs as well (Kissin et al 1996;Kaiyala et al 2001). Measuring a dependent variable continuously at steady-state drug concentrations facilitates the measurement of initial sensitivity and acute tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…A return of the measured variable toward pre-drug baseline (or control) values during a steady-state drug administration indicates acute tolerance development (Ramchandani et al, 1999;Ramsay and Woods, 1997). N 2 O is well suited for research requiring steady-state concentrations.…”
Section: Acute Tolerance and Reboundmentioning
confidence: 99%